A Study on Prevalence of Escherichia coli O157 with a Verified Method in Foods - Semiha Yalçın; Ayla Ünver Alçay; Gözde Yüzbaşıoğlu; Burcu Çakmak; Aysun Sağlam (Turkish Journal of Agriculture: Food Science and Technology)
The purpose of this study were to identify the presence of E.coli O157 and to determine its prevalence in foods which were collected from various restaurants, shops and markets in Istanbul. Also, validation of detection method of E. coli O157 in all food stuffs was carried out according to applicability, repeatability, and minimum detection limit (LOD) and false positive and negative analysis based on TS EN ISO 16654 standard method. The results showed that the prevalence of E. coli O157 in food was 2%, and its prevalence increased in April and May.